Comparison of Clinical Outcomes of Short-Course vs Long-Course Antibiotic Treatment in Children With Pyelonephritis - Zahid, Warda; Kafait, Yusra; Zahra, Anum; Kafait, Tooba; Mirza, Hamza Hussain; Saleem, Muhammad (Biological and Clinical Sciences Research Journal, 2025)
To evaluate the comparative effectiveness of short-course vs long-course antibiotic treatment for clinical outcomes of children with pyelonephritis. Methodology: A retrospective observational study was conducted in the Pediatrics Department of PIMS Hospital, Islamabad, between May 2024 and May 2025. A total of 200 children aged from 6 months to 18 years presenting in the outpatient department with urine culture showing the presence of Escherichia coli, Klebsiella species, or Proteus mirabilis were selected for the study. Children were divided into two treatment groups by physicians; Group A included 100 patients who were administered the short-course antibiotic treatment for 6-9 days, and Group B included 100 patients treated for 10 or more days. The primary endpoint was treatment failure, shown by the occurrence of one or more composite outcomes in 1 month following treatment. Results: The odds ratio of achieving the composite outcomes at follow-up between both groups was 1.19 (95% CI: 0.81-2.02). There was no significant difference between outcomes concerning age between both groups however between the age groups, children aged 4-13 years had a significantly higher frequency of treatment failure (14.7%) as compared to other age groups (9 vs 8.2%) irrespective of treatment (OR: 1.68, 95% CI: 1.12-2.81, p<0.01). 40% patients in Group A and 65% in Group B had a recurrence with an increasingly resistant organism at follow-up (OR: 0.40, 95% CI: 0.11-1.48). Conclusion: The effect of short-course and long-course antibiotic treatment is similar in children with pyelonephritis. However, short-course therapy is superior for reducing the risks of drug-resistant infection recurrence.